Experiences of Social Workers Working With Disabled Parents Who Raise Healthy Children - Jezerskytė, Edita; Stasiulaitienė, Andra (Jaunųjų mokslininkų darbai, 2015)
Nowadays the issue of social integration and support for people whit special needs have been widely discussed but little attention has been paid to the situation when they become parents. Very often they are left unattended and get support only from their family members. The aim of the paper is to analyze social workers’ experiences working with parents with special needs who raise healthy children. Research methods: scientific literature overview, semi-structured interview, qualitative content analysis. Social and psychological problems that parents with special needs face while raising children were identified. They need consultations and information on financial, logistics and psychological support, also when claiming support allowances or compensatory techniques. The importance of professional assistance and integration was also emphasised.